DOI: 10.31979/etd.cqkf-82dn
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Relationship between Creativity, Religion, and Religiosity

Abstract: AN EXPLORATORY STUDY ON THE RELATIONSHIP BETWEEN CREATIVITY, RELIGION, AND RELIGIOSITY by Kim-lien T. Nguyen Religiosity and religion are often said to be negative influences on one's creativity level. Creativity and religiosity have been looked at as a single dimension, which is a simplistic view. The purpose of this study was to examine the relationship between creativity and religiosity using scales that measure each construct multidimensionally. Religiosity was measured by one's level of inclusion of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…Regarding the negative correlation between marital satisfaction and creativity, this finding was consistent with that of Yipeng et al [32], who found that an employee's inventiveness at work is indirectly related to their quality marriage. However, the results of this study were at odds with those of Nguyen [33] and Dollinger [34], who found no connection between creativity and religiosity.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the negative correlation between marital satisfaction and creativity, this finding was consistent with that of Yipeng et al [32], who found that an employee's inventiveness at work is indirectly related to their quality marriage. However, the results of this study were at odds with those of Nguyen [33] and Dollinger [34], who found no connection between creativity and religiosity.…”
Section: Discussioncontrasting
confidence: 99%